2012
DOI: 10.1039/c2dt11647b
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective synthesis and coordination chemistry of enantiopure keto-bis-(2-phosphametallocene)s

Abstract: Enantiopure 2-(chlorocarbonyl)phosphametallocenes [MCp*(2-{COCl}-3,4-Me(2)-5-Ph-PC(4))] (M = Fe, Ru) react with phospholide anions to give 2-phosphametallocene-2'-acylphospholides K[MCp*(2-CO-2'-{3',4'-Me(2)-5'-PhPC(4)}-3,4-Me(2)-5-Ph-PC(4))] (M = Fe, Ru) and these have been converted into keto-bis-(2-phosphametallocene)s through reaction with [FeClCp*(tmeda)]; templation of this process with CuBr gives rise to the C(2)- (or pseudo-C(2)- when M = Ru) symmetric form of [{MCp*(3,4-Me(2)-5-Ph-PC(4))}(2)-2,2'-(CO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The study here is interesting because the interception of a quite strongly bound intermediate 9 sheds some light upon the reaction trajectory for the coordination of phospholide anions to late transition metal centres and also provides a rationale for a near‐perfect diastereoselectivity that is observed during the formation of 10 . Strong literature evidence suggests that the reaction of phospholide anions with late transition metal complexes involves the transient formation of η 1 ‐coordinated phospholides,3033 and this incipient η 1 ‐coordination might reasonably be expected to impose a degree of selectivity upon the reaction trajectory for the incoming metal centre. In situ NMR spectroscopic studies showed that careful treatment of phospholide 8 with two equivalents of [FeCp*(Cl)tmeda] under mild conditions (THF, 25 °C) led to complex intermediate 9 (Figure 2) quantitatively, but isolation proved difficult and single crystals suitable for characterisation could only be obtained in low yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study here is interesting because the interception of a quite strongly bound intermediate 9 sheds some light upon the reaction trajectory for the coordination of phospholide anions to late transition metal centres and also provides a rationale for a near‐perfect diastereoselectivity that is observed during the formation of 10 . Strong literature evidence suggests that the reaction of phospholide anions with late transition metal complexes involves the transient formation of η 1 ‐coordinated phospholides,3033 and this incipient η 1 ‐coordination might reasonably be expected to impose a degree of selectivity upon the reaction trajectory for the incoming metal centre. In situ NMR spectroscopic studies showed that careful treatment of phospholide 8 with two equivalents of [FeCp*(Cl)tmeda] under mild conditions (THF, 25 °C) led to complex intermediate 9 (Figure 2) quantitatively, but isolation proved difficult and single crystals suitable for characterisation could only be obtained in low yield.…”
Section: Resultsmentioning
confidence: 99%
“…We have been interested for some time in the homologation of phosphametallocenes, and the chemistry described here indicates that autotemplation may allow access to these compounds in relatively specific fashion. Whilst the precise roots of this templation are not clear at present, it should be noted that a similar diastereoselectivity is not observed in the absence of templating for the preparation of ketone‐bridged 2,2′‐keto‐bis(2‐phosphametallocene)s 33. Trinuclear phosphametallocenes are a previously unknown class, and the stability of 10 , both thermally and in air, bodes well for the preparation of more extended arrays; these seem likely to be accessible given that the protocol begins and ends with carboxymethyl‐substituted phosphametallocenes.…”
Section: Discussionmentioning
confidence: 97%